Outcome of Instrumental Vaginal Delivery at Patan Hospital - Lamichhane, Basant (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: To estimate the severity of neonatal and maternal morbidity associated with instrumental vaginal delivery (IVD). Methods: Record based cross-sectional retrospective study of 80 instrumental vaginal deliveries during two years from 2013 to 2015 were performed. Variables studied were neonatal and maternal complications. Results: Out of 80 IVD, 19(23.8%) were forceps deliveries and 61(76.2%) were vacuum deliveries. The mean one minute Apgar score was 6 and 7 for forceps and vacuum delivery respectively. The five minute Apgar score for the both IVD was 8. Regarding maternal complications 7(8.75%) cases had extended episiotomy with deep vaginal tears. In forceps delivery 5 had deep vaginal tear and one each for primary post-partum hemorrhage and urinary retention but among the vacuum deliveries two had deep vaginal tear only. Regarding neonatal complications, one had subgaleal bleed in forceps delivery and one had cephalhematoma with Erbs palsy in vacuum delivery. Conclusions: The neonatal and maternal complications between both types of IVD were comparable. Forceps and repeated vacuum application resulted in low one minute Apgar score; and extended episiotomy and deep vaginal tear were associated with use of forceps.